The influence of Cooperative Integrated Reading And Composition (CIRC) model on students' written mathematical communication skills in primary school - Ratna Pangesty, Desy Ayu; Nursirwan, Helmi; Marliah, Ari; Yasa, Lika Nurlia; Hartono, Rudi (Technium Social Sciences Journal, 2021)
This research is motivated by the lack of mathematical communication skills of grade III learners, in explaining their ideas or ideas through writing in the form of language or mathematical symbols. The purpose in this study is to find out the influence of mathematical communication skills of grade III students who obtain learning using cooperative integrated reading and composition (CIRC) model. This study is a quasi-experiment with pretest-posttest control group design,using a sample of grade III elementary school students in Cikampek Kab. Karawang 2017/2018 samples taken using Purposive Sampling technique. The total number of samples was 40 with a composition of 20 learners in the experimental group and 20 learners in the control group, fractional material with research instruments in the form of tests and non-tests. The test instrument used is a description question to measure students' mathematical communication skills, while for student activities seen from the student's daily journal. The results showed that: 1) There is an influence of cooperative integrated reading and composition (CIRC) model on students' mathematical communication skills. 2) There are differences in students' mathematical communication skills between classes that study using cooperative integrated reading and composition (CIRC) models and conventional models. 3) Student activity increases after learning using cooperative integrated reading and composition (CIRC) model. This proves that the Cooperative Integrated Reading and Composition (CIRC) model affects students' mathematical communication skills.